The Abundance and Diversity of Arboreal Ants in Northern Australia - Majer, Jonathan (1990)
This paper collates survey data on the abundance and diversity of arboreal ants in subtropical and tropical rain forests in northern Australia. Data on arboreal ants in nearby Eucalyptus forests and also from Eucalyptus vegetation in southwest Australia are presented for comparison. The diversity of arboreal ants, both tree- and ground-nesting, is low in Australian rain forests in comparison with other tropical regions and it is sometimes lower than that of nearby Eucalyptus forest. Except where Oecophylla smaragdina, or perhaps certain Crematogaster spp. are present, the trees of the tropical and subtropical rain forests lack dominant ants. Reasons for the low diversity of, and degree of dominance by arboreal ants in Australian rain forests are speculated upon. Reasons include the possibility that the role of ants has been replaced by some other taxon; the strong seasonal climate or the productivity of such forests may limit the abundance of ants; arboreal ants may be limited by competition from ground-dwelling ants; or, alternatively, there may be some biogeographic explanation.